Beratung im Kontext des Lebenslangen Lernens Konzepte, Organisation, Politik, Spannungsfelder - Dörner, Olaf; Iller, Carola; Maier-Gutheil, Cornelia; Schiersmann, Christiane; Schüßler, Ingeborg (Schriftenreihe der Sektion Erwachsenenbildung der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE), 2019)
The volume is devoted to the increasing importance of advice in the context of lifelong learning. The contributions deal with the actors, concepts and organizations of advice as an opportunity for support as well as the strategic use of advice as a political control instrument. Counseling is thus taken into account as an ambivalent and differentiated phenomenon in modern societies and examined for its importance for adult education.